OTA a wide common mode low power - Gómez-Ortiz, Héctor Iván; Angarita-Cediel, Francisco; Neira-Triana, Carlos Andrés (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
This paper presents the design of an operational transconductance amplifier OTA operating in sub-threshold region for low power consumption. Simulations were performed in SYNOPSYS tools program for a 180nm technology. The differential amplifier is supplied with a VDD of 600mV, and has a load capacitance of 15pF. Amplifier gain is 60.08dB with unity-gain frequency of 21.7kHz, and a phase margin greater than 50degrees. Wide common mode operation is achieved by using complementary input differential pairs (NMOS and PMOS) showing a range of operation of 500mV.